Near-roadway air pollution exposure and altered fatty acid oxidation among adolescents and young adults – The interplay with obesity. (September 2019) - Chen, Zhanghua; Newgard, Christopher B.; Kim, Jeniffer S.; IIkayeva, Olga; Alderete, Tanya L.; Thomas, Duncan C.; Berhane, Kiros; Breton, Carrie; Chatzi, Leda; Bastain, Theresa M.; McConnell, Rob; Avol, Edward; et al.
Abstract: Background: Air pollution exposure has been shown to increase the risk of obesity and metabolic dysfunction in animal models and human studies. However, the metabolic pathways altered by air pollution exposure are unclear, especially in adolescents and young adults who are at a critical period in the development of cardio-metabolic diseases. Objectives: The aim of this study was to examine the associations between air pollution exposure and indices of fatty acid and amino acid metabolism. Methods: A total of 173 young adults (18–23 years) from eight Children's Health Study (CHS) Southern California communities were examined from 2014 to 2018. Near-roadway air pollution (NRAP) exposure (freeway and non-freeway) and regional air pollution exposure (nitrogen dioxide, ozone and particulate matter) during one year before the study visit were estimated based on participants' residential addresses. Serum concentrations of 64 targeted metabolites including amino acids, acylcarnitines, non-esterified fatty acid (NEFA) and glycerol were measured in fasting serum samples. Principal component analysis of metabolites was performed to identify metabolite clusters that represent key metabolic pathways. Mixed effects models were used to analyze the associations of air pollution exposure with metabolomic principal component (PC) scores and individual metabolite concentrations adjusting for potential confounders. Results: Higher lagged one-year averaged non-freeway NRAP exposure was associated with higher concentrations of NEFA oxidation byproducts and higher NEFA-related PC score (all p 's ≤ 0.038). The effect sizes were larger among obese individuals (interaction p = 0.047). Among females, higher freeway NRAP exposure was also associated with a higher NEFA-related PC score ( p = 0.042). Among all participants, higher freeway NRAP exposure was associated with a lower PC score for lower concentrations of short- and median-chain acylcarnitines ( p = 0.044). Conclusions: Results of this study indicate that NRAP exposure is associated with altered fatty acid metabolism, which could contribute to the metabolic perturbation in obese youth. Highlights: Near-roadway air pollution exposure is associated with altered fatty acid metabolism Near-roadway air pollution exposure interacts with obesity and sex in the association with fatty acid metabolism. Air pollution may contribute to the metabolic dysfunction in youth through lipolysis and altered fatty acid metabolism